A New Paradigm of Madrasah Learning in the Implementation of Merdeka Curriculum - Hazyimara, Karunia (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2023)
The condition of Indonesian education is still weak as shown by several surveys regarding the quality of education. This is made worse by pandemic conditions which require the learning system to adapt to the conditions that occur. Indonesia is experiencing learning loss so it needs to be overcome optimally to improve the quality of Indonesian education. This research aims to analyze the new paradigm of Indonesian education, especially in madrasah, which occurred after the policy of using the Merdeka curriculum. Madrasah as one of the educational institutions that are characterized by Islamic content must be able to adapt to the current curriculum and the increasingly developing times. This research was conducted using library research with a descriptive-qualitative research approach. To support the method used, researchers collected data through documentation obtained from searching for written data regarding the themes raised. The results of the research conducted show that the Merdeka curriculum is designed to overcome the backwardness of Indonesian education and align with technological developments. Madrasah is one of the Indonesian educational units that participates in efforts to educate the Indonesian nation through the Merdeka curriculum. The new paradigm for madrasah in implementing the Merdeka curriculum lies in the use of constructivism theory, making madrasah a means of strengthening students' character and developing skills, flexible and using a differentiated learning approach, and integrated with technology.